СОЦИОПРАГМАТИЧЕСКОЕ ИЗМЕРЕНИЕ ТРАНСЛАТОЛОГИЧЕСКОЙ ПАРАДИГМЫ: КОММУНИКАТИВНОЕ ДЕЙСТВИЕ В ПЕРЕВОДЕ - Mityagina, Vera A (Vestnik Volgogradskogo gosudarstvennogo universiteta. Serii͡a︡ 2, I͡A︡zykoznanie., 2017)
The article reveals the explantatory and heuristic possibilities of the socio-pragmatic approach to the analysis of translation based on the use of the typology of communicative actions conditioned by discourse conventions. The relevance of the research is explained by the fact that provisions of the discourse theory and the communication theory are not widely used to study the procedural activity of a translator. The material of the research is represented by globalized (translated into English) and localized (translated into Russian and German) texts of dynamically developing tourism Internet discourse. The author interprets the communicative action as a procedural unit of research that makes it possible to understand the logic of the translated actions that create the text of translation, and proves the provision (assumption?), that the preservation / change of the type of communicative action explains translational transfromations, since the socio-cultural semiosis in the intercultural space is created by texts as complex communicative signs. Overcoming the resistance of the translation language system is considered by the author to be a formal component of the transformations underway, and it is suggested to distinguish the characteristics of communicative activities determined by discourse as their content component. This approach provides new arguments in favor of understanding translation as a cultural transfer. A translation solution, based on the consideration of the communicative potential of a particular fragment of the text, allows the creation of a secondary text as a communicative sign responsible for the implementation of a comprehensive socio-pragmatic program.